Play it again: how game-based learning improves flow in Accounting and Marketing education - Silva, Rui Jorge Rodrigues da (2020)
Flow theory is used in this article [Csikszentmihalyi, M. (1990). The domain of creativity] to determine whether gamified resources, named Accountingame and Marketingame, possess certain characteristics which, in the form of educational games, increase the performance of Portuguese undergraduate students attending Accounting (N= 816) and Marketing (N= 195) curricular units for the first time. A structural equation model was used to look into the direct effects of the characteristics of the game, such as Concentration, Clarity, Feedback, Challenge, Autonomy, Social Interaction, and Perceived Learning, on students’ learning Flow. Results clearly show that, with the exception of Feedback, all the other dimensions were Flow predictors. Overall, by introducing games into the curriculum, students’ motivation and interest increased and demonstrates that games can be an effective way for students to learn.